Aberrant RET expression impacts on normal mammary gland post-lactation transition enhancing cancer potential - Vallone, Sabrina Aldana (2022)
RET is a receptor tyrosine kinase with oncogenic potential in the mammary epithelium. Several receptors with oncogenic activity in the breast are known to participate in specific developmental stages. We found that RET is differentially expressed during mouse mammary gland development: RET is present in lactation and its expression dramatically decreases in involution, the period during which the lactating gland returns to a quiescent state after weaning. Based on epidemiological and pre-clinical findings, involution has been described as tumor promoting. Using the Ret/MTB doxycycline-inducible mouse transgenic system we show that sustained expression of RET in the mammary epithelium during the post-lactation transition to involution is accompanied by alterations in tissue remodeling and an enhancement of cancer potential. Following constitutive Ret expression we observed a significant increase in neoplastic lesions in the post-involuting versus the virgin mammary gland. Furthermore, we show that abnormal RET overexpression during lactation promotes factors that prime involution, including premature activation of Stat3 signaling and, using RNA-seq, an acute-phase inflammatory signature. Our results demonstrate that RET overexpression negatively affects the normal post-lactation transition.